Regulation of NKCC2 splicing and phosphorylation. Issue 5 (September 2015) - Schießl, Ina Maria; Castrop, Hayo
<x xml:space="preserve">Abstract</x> Purpose of review Transepithelial salt transport in the thick ascending limb of Henle's loop (TAL) crucially depends on the activity of the Na/K/2Cl cotransporter NKCC2. The pharmacologic blockade of NKCC2 leads to pronounced natriuresis and diuresis, which indicate key roles for NKCC2 in renal salt retrieval. The inadequate regulation of NKCC2 and the loss of NKCC2 function are associated with the disruption of salt and water homoeostasis. This review provides a specific overview of our current knowledge with respect to the regulation of NKCC2 by differential splicing and phosphorylation. Recent findings Several mechanisms have evolved to adapt NKCC2 transport to reabsorptive needs. These mechanisms include the regulation of NKCC2 gene expression, the differential splicing of the NKCC2 pre-mRNA, the membrane trafficking, and the modulation of the specific transport activity. Substantial progress has been made over the past few years in deciphering the function of kinases in the regulatory network controlling NKCC2 activity and in elucidating the underlying mechanism and the functional consequences of the regulated differential splicing of the NKCC2 pre-mRNA. Summary NKCC2 differential splicing and phosphorylation are critically involved in the modulation of the thick ascending limb of Henle's loop reabsorptive capacity and, consequently, in salt homoeostasis, volume regulation, and blood pressure control.